Egyptian Public Law Judge: Reviewing Public Economic Policies from Nationalization to Privatization - el Menshawy, Omar (AUC Knowledge Fountain, 2021)
Do public law judges play a role in public economic policies in Egypt? Egypt has witnessed rough changes, leading to the adoption of different public economic policies. Public law judges have played a key role in these economic shifts. However, the efficacy of this role is pending on the satisfaction or dissatisfaction of the government with the courts and the judicial decisions. This paper argues that the government posses the upper hand in dealing with the judicial influence in economic issues in Egypt. The paper scrutinizes the transformation in the judicial attitude towards government economic policies. Specifically, the paper demarcates the extent to which the role of the public law judge has affected the public economic policies in Egypt, and portrays the reaction of the government towards the effects of these rulings. This paper argues that the government views courts’ judgments according to its own economic policies. Practically, the government will appreciate courts’ judgments if courts confer legitimacy on the controversial economic policies of the government, or if the judicial intervention is compatible with the government economic directions, while the government will hinder the impact of courts’ contributions if the courts’ decisions go against its willingness. In that case, the government can reverse court policy through enacting legislation that deprives courts’ judgments from its crucial effects or restricts the scope of the judicial review of the public law judge itself. To that end, the paper highlights the Supreme Constitutional Courts’ rulings in the economic sphere and how the court helped the regime dismantle the legal infrastructure of the socialist economic era in order to pave the way for the implementation of the new-liberal economic policies. In the same context, the Council of State Courts issued many noticeable judgments that annulled many privatization contracts for illegality and corruptions in a way that touched the essence of the neo-liberalism system. The paper also argues that Law No.32 of the year 2014 is an explicit example for how the government determines the limits and extent of the judicial influence in economic sphere in order to secure its economic policies.